Pengaruh Model Pembelajaran Problem Solving- Think Pair Share terhadap Pengetahuan Metakognitif Siswa - Sandi Limbanadi; Subandi Subandi; Munzil Munzil (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study aims to determine the students' metacognitive knowledge chemistry students who study with Problem Solving-Think Pair Share Learning Models in the experimental class and problem solving learning models in the control class. The study uses a posttest control group design and sample selection uses convenience sampling techniques. Research data in the form of metacognitive knowledge test values measured from test questions in the form of essays each containing three types of metacognitive knowledge. The results has showed that there was a influence of learning models on students' metacognitive knowledge, this effect was seen from the existence of significant differences between students studying in the experimental class. Abstrak: Penelitian ini bertujuan untuk mengetahui pengetahuan metakognitif siswa kimia materi sifat koligatif larutan pada siswa yang belajar dengan model pembelajaran Problem Solving-Think Pair Share di kelas eksperimen dan model pembelajaran Problem Solving di kelas kontrol. Penelitian menggunakan desain Postest Control Group Design dan pemilihan sampel menggunakan teknik Convenience Sampling. Data penelitian berupa nilai tes pengetahuan metakognitif yang diukur dari soal tes berbentuk esai masing-masing berisi tiga jenis pengetahuan metakognitif. Hasil penelitian menunjukkan bahwa siswa yang belajar dengan model pembelajaran Problem Solving-Think Pair Share memiliki pengetahuan metakognitif yang lebih baik dibandingkan yang belajar dengan model Problem Solving.